Thematic issue of Nomad – Call for papers - Eskeland Rangnes, Toril; Meaney, Tamsin (NOMAD Nordic Studies in Mathematics Education, 2016)
Learning mathematics in linguistically diverse classrooms – research perspectives from the Nordic countries ...